Exploring the relationships among innovation, financial sector development and environmental pollution in selected industrialized countries. (15th April 2021) - Ibrahim, Muazu; Vo, Xuan Vinh
Abstract: The Paris Climate Conference commits countries to contribute to reducing global warming through a Nationally Determined Contributions (NDCs) which implore on countries to reduce emissions for improved environmental quality. Recognizing the importance of innovation and financial sector development to environmental quality, several countries have embarked on identifying ways to improve environmental quality. However, studies on the tripartite linkages among innovation, financial development and pollution relationships have produced mixed findings. Furthermore, a plethora of the existing studies have relied on only carbon dioxide (CO2 ) emissions thus neglecting other anthropogenic activities which impact on the environment. More tellingly, how countries' levels of innovation moderate financial development–pollution link is yet to be studied. By relying on data from 27 selected industrialized countries spanning 1991–2014 in examining the tripartite relationships, we find that, while innovation lowers environmental pollution, beyond a certain threshold level, higher innovation exacerbates environmental degradation. Furthermore, while improved financial development increases pollution, higher innovation dampens the environmental quality–reducing effect of finance. Results from our panel causality tests also reveal a feedback causal linkage between innovation and ecological footprint, and a one-way causality from CO2 emissions to innovations. However, irrespective of the indicator of environmental pollution, financial development and pollution evolve independently, albeit differences at the country levels. Highlights: Innovation-environmental pollution is U-shaped. Improved financial development increases pollution. Unbridled innovation dampens the environmental quality–reducing effect of finance. Financial development and pollution evolve independently.